Evaluation of Using Modern Teaching Methods Benefits in Dentistry by the Teachers' View at the Medical Faculty of Palacky University, Olomouc - Ľ. Harvan; J. Stejskalová (Czech Dental Chamber, 2012)
Introduction: There are huge possibilities of modern information and communication technologies application in dentistry. Nowadays we use them from the first moment of the patient's visit to the dentist's office. This is mainly an electronic form of all patient documentation as well as the methods of diagnosis and treatment based on the use of computers or a variety of multimedia means that allows us to reach better explaination the aims and course of the treatment to the patient. Besides diagnosis and treatment, the information and communication technologies can be applied in dentistry students' teaching process. It comprises e-learning training which presently is being become very popular in universities' teaching process. Another ways of information and communication technologies application in dentistry teaching are electronic atlases contained 3D models, simulations and animations, educational video, lecture in electronic form etc. Aims: The work is aimed at assessment of using modern teaching methods benefits (e-learning) in dentistry according to teachers' poll. Another objective was to find teachers' eventual interest in participation in improving and developing e-course. Methods: Prior to the investigation, the pilot e-course has been published on the Clinic of Dental Medicine's web site (Medical Faculty and Faculty Hospital, Palacky University in Olomouc). This course is as addition to dentistry teaching. The application of modern information and communication technologies benefits in dentistry teaching was evaluated by teachers' poll. The group of respondents consisted of 43 dentistry teachers with age of 24-75 years including pedagogic practice size of 1-50 years. The special questionnaire was used for the researching targets. This questionnaire allowed to estimate teachers opinion of modern teaching methods application in dentistry as well as to determine if the teachers arise their interest in participation in further development of e-course.Data received were statistically worked up according to Fisher exact test, Shapiro-Wilk normality test and Mann-Whitney U-test. Results: The total return of the questionnaires was 100%. One of the basic questions was the issue about "e-learning" term background. This term was clear to all of the teachers. The greater part of educators (69.8%) assumes that e-learning can provide a positive influence on students' professional qualities. Among the group of teachers with interest in e-learning size of pedagogic practice was 1-50 years including average value of 15 years and standard deviation of 16.7. The average value in this group was 6.5 years. Among the group of teachers having no interest in e-learning size of pedagogic practice was 0.2-40 years including average value of 11.9 years and standard deviation of 13.6. The average value in this group was 5 years. Conclusions: Investigation results showed the teachers' interest in modern information and communication technologies application in dentistry classic teaching. Thus, the teaching with electronic elements seems to be very beneficial and attractive. Many teachers are ready to participace in developing further e-courses.